Mapping and tracking the complexity of financial flows through non-state non-profit (faith-based) health providers in Kenya - Kingangi, Lucy (Health Policy and Systems Division, 2018)
In strengthening health systems, the World Health Report 2000 indicates that health system improvement strategies must also cover private (for-profit and non-profit) health care provision and financing if progress towards Universal Health Coverage is to be achieved. Yet very little is known about the financing of non-profit providers in Africa - especially not faith-based health providers, who have often historically remained elusive in terms of financial transparency. This thesis reports on a multiple case study conducted with two non-profit faith-based health providers in Kenya, namely the Africa Inland Church Kijabe Hospital; and Nyumbani-Children of God Relief Institute in Nairobi (Nyumbani) - and situates these within the broader context of health systems financing and public-private partnership in Kenya. Data was collected from multiples sources including: secondary literature; secondary analysis of existing data (such as the Kenya Health Information System); financial data on projects and annual reports; routine facility and service data; previous research on both organizations; archival data; and supplemented by 6 in-depth interviews with key stakeholders. The study reveals a highly complex funding environment for non-profit (and faith-based) health providers in Kenya, which is a result of historic health system configurations, and current funding policy and focus (such as the influx of HIV-related funding). The HIV program in AIC Kijabe Hospital is solely funded by USAID; while Nyumbani is also funded by USAID (70%), but has other private sources. In both cases, funding from various sources is structured differently with varied financial flows and requirements. Faith-based health providers in Kenya are highly dependent on complex donor-funding arrangements, and lack financial resilience as a result. Donors need to better understand the nuance of engagement with such providers.